CO2 CAPTURE USING DISSOLVED AMMONIA (NH4OH) - ARTICLE REVIEW - Nuryoto, Nuryoto; Demustila, Harly; Rahmayetty, Rahmayetty (Jurnal Rekayasa Mesin, 2025)
The rise in carbon dioxide (CO₂) emissions has accelerated efforts to develop environmentally sustainable alternative carbon capture and utilization technologies. Among the promising approaches is the use of ammonium hydroxide (NH₄OH) for CO₂ capture. The objective of this study is to systematically investigate the influence of CO₂ flow rate, temperature, pH, NH₄OH concentration, and stirring speed on the performance of CO₂ capture, as determined through a comprehensive literature review. The review findings demonstrate that each of these variables plays a critical role in enhancing CO₂ capture efficiency, as evidenced by the increased percentage of CO₂ removed. Temperature and pH directly influence the chemical equilibrium of the reaction, whereas stirring improves the diffusion of gas into the liquid medium. The interrelated effects of these parameters highlight the necessity of adopting a systematic approach to process optimization. In conclusion, an in-depth understanding of these influencing factors is essential for the development of a robust and sustainable CO₂ capture system. It is recommended that future studies incorporate integrated experimental research, process modeling, environmental impact evaluations, and product analyses to support the scaling up of this technology for mini-plant and commercial-scale implementation.